6-Aryl-quinazolines as novel GABAB receptor positive allosteric modulators. (1st July 2022) - Huszár, József; Petró, József Levente; Hadady, Zsuzsa; Bobok, Amrita Ágnes; Sághy, Katalin; Halász, Attila Sándor; Hornyánszky, Gábor; Román, Viktor; Greiner, István; Éles, János
Graphical abstract: Abstract: The systemic use of GABAB orthosteric agonist baclofen might be limited due to its detrimental properties: sedation and motor impairment. In contrast, GABAB positive allosteric modulators produce less adverse effects. Using BHF-177 as a starting point, we found a new active scaffold: the 6-aryl-quinazoline scaffold. Further elaborating the scaffold, we identified several in vitro and in vivo active compounds.